Pharmacist‐led, video‐stimulated feedback to reduce prescribing errors in doctors‐in‐training: A mixed methods evaluation. Issue 10 (23rd August 2019) - Parker, Hazel; Farrell, Odran; Bethune, Rob; Hodgetts, Ali; Mattick, Karen
Abstract : Aims: To develop and evaluate a feasible, authentic pharmacist‐led prescribing feedback intervention for doctors‐in‐training, to reduce prescribing errors. Methods: This was a mixed methods study. Sixteen postgraduate doctors‐in training, rotating though the surgical assessment unit of 1 UK hospital, were filmed taking a medication history with a patient and prescribing medications. Each doctor reviewed their video footage and made plans to improve their prescribing, supported by feedback from a pharmacist. Quantitative data in the form of prescribing error prevalence data were collected on 1 day per week before, during and after the intervention period (between November 2015 and March 2017). Qualitative data in the form of individual semi‐structured interviews were collected with a subset of participants, to evaluate their experience. Quantitative data were analysed using a statistical process chart and qualitative data were transcribed and analysed thematically. Results: During the data collection period, 923 patient drug charts were reviewed by pharmacists who identified 1219 prescribing errors overall. Implementation of this feedback approach was associated with a statistically significant reduction in the mean number of prescribing errors, from 19.0/d to 11.7/d (estimated to equate to 38% reduction; P < .0001). Pharmacist‐led video‐stimulated prescribing feedback was feasible and positively received by participants, who appreciated the reinforcement of good practice as well as the opportunity to reflect on and improve practice. Conclusions: Feedback to doctors‐in‐training tends to be infrequent and often negative, but this feasible feedback strategy significantly reduced prescribing errors and was well received by the target audience as a supportive developmental approach.